The State of Indonesia’s Marriage Law: 50 Years of Statutory and Judicial Reforms - Wirastri, Theresia Dyah; van Huis, Stijn Cornelis (AHKAM : Jurnal Ilmu Syariah, 2024)
Because of its entanglement with religious norms, Muslim family law reform is a sensitive issue. In Indonesia, the validity, rights, and responsibilities pertaining to Muslim marriage and divorce are regulated by the 1974 Marriage Law and the 1991 Compilation of Islamic Law. The 1974 Marriage Law is both general and pluralistic in character, since it introduced general reforms applying to all religions, while leaving other matters to the legal regimes attached to a person’s religion. Muslim family law norms, including several new reforms, were subsequently laid down in the 1991 Compilation of Islamic Law. After 1991, statutory reform of Muslim family law stalled, as differences in opinion between liberal and conservative Muslims proved unbridgeable. This paper argues that, despite these divisions, reform continued – not by actions of the legislative, but by actions of the courts. These actions take two forms: first, the form of court decisions, specifically “activist” judgments by the Supreme Court and judicial review decisions by the Constitutional Court; and second, the form of Supreme Court guidelines that following the introduction of the chamber system in 2011 are issued annually by means of Supreme Court Circulars. By reinterpreting family law norms in light of women’s and children’s rights, we will show how courts initiated significant non-statutory reforms of Muslim family law. Thus, exactly 50 years following the birth of the 1974 Marriage Law, we shed new light on the role of judicial institutions in reforming and reinterpreting Muslim family law in Indonesia. Abstrak:Reformasi hukum keluarga Islam selalu menjadi isu sensitif karena berkelindan dengan norma-norma agama. Di Indonesia, keabsahan, hak, dan tanggung jawab perkawinan dan perceraian diatur dalam Undang-Undang Perkawinan Tahun 1974 (UU Perkawinan 1974) dan Kompilasi Hukum Islam (KHI) Tahun 1991. UU Perkawinan 1974 merupakan produk hukum yang umum dan plural. Artinya, UU Perkawinan 1974 memperkenalkan reformasi yang berlaku untuk semua agama, namun rezim hukum yang berlaku bergantung pada agama yang dianut. Norma hukum keluarga Islam, termasuk beberapa reformasi baru, kemudian ditetapkan dalam KHI. Setelah tahun 1991, reformasi hukum keluarga berjalan dengan lambat karena perbedaan pendapat antara kelompok Muslim liberal dan konservatif tidak dapat dijembatani dengan baik. Melalui artikel ini kami berargumentasi bahwa terlepas dari perbedaan pendapat tersebut, reformasi hukum keluarga tetap berjalan – tidak melalui perubahan undang-undang melainkan melalui lembaga peradilan. Reformasi ini terjadi dalam dua bentuk: Pertama, dalam bentuk putusan pengadilan, terutama melalui putusan yang bernuansa “aktivisme” oleh Mahkamah Agung dan hasil uji materiil oleh Mahkamah Konstitusi. Kedua, melalui pedoman yang dikeluarkan oleh Mahkamah Agung setiap tahunnya, dalam bentuk Surat Edaran Mahkamah Agung sebagai implikasi dari pemberlakuan sistem kamar pada tahun 2011. Lembaga peradilan, melalui reinterpretasi terhadap norma hukum keluarga yang mengedepankan hak perempuan dan anak, telah menghasilkan reformasi hukum keluarga yang signifikan melalui mekanisme di luar perubahan UU Perkawinan. Dengan demikian, tepat 50 tahun sejak lahirnya UU Perkawinan 1974, artikel ini menyoroti peran lembaga yudikatif dalam mereformasi dan menafsirkan ulang hukum keluarga Islam di Indonesia.